2020
DOI: 10.1109/access.2020.2990080
|View full text |Cite
|
Sign up to set email alerts
|

Study of Multimodal Interfaces and the Improvements on Teleoperation

Abstract: Research in multimodal interfaces aims to provide immersive solutions and to increase overall human performance. A promising direction is to combine auditory, visual and haptic interaction between the user and the simulated environment. However, no extensive comparison exists to show how combining audiovisuohaptic interfaces would affect human perception and by extent reflected on task performance. Our paper explores this idea and presents a thorough, full-factorial comparison of how all combinations of audio,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 61 publications
3
49
0
Order By: Relevance
“…V. DISCUSSION Our findings agree with previous studies, where bimodal feedback increased the accuracy and precision in contact tasks [3]. Also, our results are in accordance with a meta-analysis of user interaction studies, where the bimodal (i.e., visuohaptic) feedback was found to improve performance [19].…”
Section: Subjective Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…V. DISCUSSION Our findings agree with previous studies, where bimodal feedback increased the accuracy and precision in contact tasks [3]. Also, our results are in accordance with a meta-analysis of user interaction studies, where the bimodal (i.e., visuohaptic) feedback was found to improve performance [19].…”
Section: Subjective Resultssupporting
confidence: 92%
“…Rennes, IRISA, Inria -Rennes 35042, France. name.surname@irisa.fr 3 M. Marchal is with the Univ. Rennes, INSA, IRISA, Inria, CNRS -35042 Rennes, France and Institut Universitaire de France.…”
Section: Introductionmentioning
confidence: 99%
“…One study investigated 3D virtual hand pointing with the index finger in addition to incorporating vibration feedback using a 3D screen display [63]. While disregarding depth and spatial arrangements, contrary to [5,59], they found that vibration feedback provides a reasonable addition to visual feedback, which appears to be in line with existing literature on multi-modal interfaces [2,60,82]. This is furthermore confirmed by numerous neuroscience studies indeed confirming that the simultaneous presence of both visual and somatosensory sensory cues is beneficial, particularly due to both modalities overlapping in the same brain region [1,3,36,73].…”
Section: Q12supporting
confidence: 65%
“…However, during object interaction, be it pointing or manipulation, rotation is a fundamental part. When performing a task that requires some kind of spatial accuracy, we humans usually attempt to match the rotation of the object so it satisfies certain spatial criteria [82]. Stoelen and Akin [77], were the first to combine both translational and rotational movements in one experiment.…”
Section: Translation or Rotation?mentioning
confidence: 99%
See 1 more Smart Citation